2021
DOI: 10.1111/aos.15007
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CD146 attenuates retinal neovascularization via vascular endothelial growth factor receptor 2 signalling pathway in proliferative diabetic retinopathy

Abstract: Purpose To investigate the expression of CD146 and its role in proliferative diabetic retinopathy (PDR). Methods Enzyme linked immunosorbent assay was performed to analyse the expression and relationship of sCD146, vascular endothelial growth factor (VEGF), sVEGFR1 and sVEGFR2 in vitreous specimens from PDR and idiopathic epiretinal membranes (IERM) or idiopathic macular hole patients. The location of CD146 in ERMs was detected by immunofluorescence. The oxygen‐induced retinopathy (OIR) mice model was establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Joshkon et al (2020) reported that CD146 and its soluble form play a major role in physiological and pathological angiogeneses. Moreover, CD146 is involved in angiogenesis as a co‐receptor for vascular endothelial growth factor receptor 2 (FLK1), which is involved in vascular endothelial cell development and proliferation (Jiang et al, 2012; Lin et al, 2022). Therefore, CD146 likely induces blood vessels in the area before dentin formation begins (Figure 7b).…”
Section: Discussionmentioning
confidence: 99%
“…Joshkon et al (2020) reported that CD146 and its soluble form play a major role in physiological and pathological angiogeneses. Moreover, CD146 is involved in angiogenesis as a co‐receptor for vascular endothelial growth factor receptor 2 (FLK1), which is involved in vascular endothelial cell development and proliferation (Jiang et al, 2012; Lin et al, 2022). Therefore, CD146 likely induces blood vessels in the area before dentin formation begins (Figure 7b).…”
Section: Discussionmentioning
confidence: 99%